Pembatalan Pengangkatan Anak Oleh Pengadilan - Wida Sukma Karomah; Prihati Yuniarlin (Jurnal Preferensi Hukum, 2025)
Child adoption represents a solution for married couples unable to have biological children, serving as an alternative path to complete their family happiness. However, the adoption process doesn't always proceed smoothly, and there have been cases where adoption decisions are later annulled. This study examines the legal challenges surrounding adoption annulment cases that have received district court determinations, focusing on the possibility of canceling adoption decisions and their legal consequences. Using normative juridical research methods, this study collected secondary data through literature review and interviews. The findings reveal that adoption annulment becomes possible due to the lack of concrete regulations in existing laws, leaving litigation as the only resolution mechanism. The legal implications of such annulments include the termination of all civil relationships between adopted children and their adoptive parents, resulting in the child's return to their biological parents. This research recommends the development of more comprehensive regulations regarding adoption annulment mechanisms to provide legal certainty for all parties involved.